H2 dissociation by H+ and He2+ projectiles at intermediate energies - Martínez, Sergio Hernán (2003)
We have investigated proton emission from dissociated H2 molecules after colliding with H+ and He2+ ions with energies 25, 50 and 100 keV amu-1. The energy spectra of protons have been obtained covering the angular range from 10° to 170° and fragment energies from 3-15 eV for He2+ projectiles and in the 0-15 eV range for H+ impact, respectively. Using the Franck-Condon approximation we were able to find the relative contributions for some dissociation channels (2pπu, 2sσg, 2pσu and Coulomb explosion (CE)). For He2+ projectiles we found that the momentum transfer to the target must be included in the model to obtain a better description of the experimental results. When compared to the H+ impact case, we observe for He2+ projectiles the enhancement of the CE channel due to higher capture probabilities. Differential cross sections as a function of emission angle were obtained to investigate the orientation dependence of the electronic processes leading to dissociation. Total cross sections are also estimated and compared to measurements from other laboratories.